2016
DOI: 10.1044/2016_jslhr-s-14-0137
|View full text |Cite
|
Sign up to set email alerts
|

The Palin Parent Rating Scales: Parents' Perspectives of Childhood Stuttering and Its Impact

Abstract: The Palin Parent Rating Scale is a valid and reliable tool, providing a method of exploring parents' perceptions of stuttering, the impact it has on the child and themselves, and the parents' knowledge of and confidence in managing the stuttering. This is an important addition to the existing range of assessments that may be used to evaluate stuttering in children up to age 14;6 (years;months) and allows the wider targets of parent-led therapy programs to be evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 21 publications
3
37
0
Order By: Relevance
“…Smith and Weber (2016) highlighted the challenges of developing reliable and valid measures of emotional factors in young children, which also relate to the challenges of measuring how children are affected by stuttering. Parental reports have commonly been used in investigating the impact of stuttering (e.g., Langevin et al, 2010;Millard & Davis, 2016). However, as no study to date has targeted agreement between child and parent report by application of the same instrument for both groups, the level of agreement between children and parents remains unclear.…”
Section: Measurement Of Impact Of Stutteringmentioning
confidence: 99%
See 1 more Smart Citation
“…Smith and Weber (2016) highlighted the challenges of developing reliable and valid measures of emotional factors in young children, which also relate to the challenges of measuring how children are affected by stuttering. Parental reports have commonly been used in investigating the impact of stuttering (e.g., Langevin et al, 2010;Millard & Davis, 2016). However, as no study to date has targeted agreement between child and parent report by application of the same instrument for both groups, the level of agreement between children and parents remains unclear.…”
Section: Measurement Of Impact Of Stutteringmentioning
confidence: 99%
“…In recent decades, a number of studies have investigated the consequences of stuttering for the youngest affected population: children aged two to six years (referred to hereafter as young children). While investigations of impact have depended mainly on parental reports (e.g., Langevin, Packman & Onslow, 2010;Millard & Davis. 2016), studies targeting communication attitudes have commonly used self-reporting from the age of three (e.g., Brce & Vanryckeghem, 2017;Clark et al, 2012;Vanryckeghem, De Niels, & Vanrobaeys, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted by Millard et al utilized the Palin Parent Rating Scale, which was specifically prepared for stuttering, and assessed the familial perspective. Their findings showed that parents are anxious about stuttering (14) . Profiling parent anxiety levels is significant due to the following reasons: first, the anxiety levels of parents may refer to a psychopathology per se and this should be managed (10) ; second, the parents' anxiety can be conveyed to their children, and this situation may have a negative impact on the long-term reaction the children towards stuttering (14) .…”
Section: Studies On Resilience Social Support and Trait Anxiety Levelsmentioning
confidence: 99%
“…Their findings showed that parents are anxious about stuttering (14) . Profiling parent anxiety levels is significant due to the following reasons: first, the anxiety levels of parents may refer to a psychopathology per se and this should be managed (10) ; second, the parents' anxiety can be conveyed to their children, and this situation may have a negative impact on the long-term reaction the children towards stuttering (14) . In addition, the role of parents is a key factor in modeling resilient responses to children and creating a resilience-rich environment.…”
Section: Studies On Resilience Social Support and Trait Anxiety Levelsmentioning
confidence: 99%
See 1 more Smart Citation